2020
DOI: 10.1002/ehf2.12633
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral endothelial dysfunction in myalgic encephalomyelitis/chronic fatigue syndrome

Abstract: Aims Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is a complex multisystem disease. Evidence for disturbed vascular regulation comes from various studies showing cerebral hypoperfusion and orthostatic intolerance. The peripheral endothelial dysfunction (ED) has not been sufficiently investigated in patients with ME/CFS. The aim of the present study was to examine peripheral endothelial function in patients with ME/CFS. Methods and results Thirty-five patients [median age 40 (range 18-70) years, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 38 publications
7
60
0
Order By: Relevance
“…To the best of our knowledge, this is the first study to assess pre-and-post measures of AIx75 and PWV after a maximal exercise bout in ME/CFS. It has been demonstrated that ME/CFS patients suffer from impaired vascular function, identified from other measures such as the reactive hyperemia scale [ 20 ], markers of inflammation and oxidative stress [ 5 , 10 ], heart rate and blood pressure variability [ 26 ] as well as AIx75 and PWV [ 6 , 27 ]. Expanded research also suggests that completing physical activity may exacerbate ME/CFS symptoms and provoke an increased oxidative and inflammatory response [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first study to assess pre-and-post measures of AIx75 and PWV after a maximal exercise bout in ME/CFS. It has been demonstrated that ME/CFS patients suffer from impaired vascular function, identified from other measures such as the reactive hyperemia scale [ 20 ], markers of inflammation and oxidative stress [ 5 , 10 ], heart rate and blood pressure variability [ 26 ] as well as AIx75 and PWV [ 6 , 27 ]. Expanded research also suggests that completing physical activity may exacerbate ME/CFS symptoms and provoke an increased oxidative and inflammatory response [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increased presence of CRP levels was also found in the CFS cohort compared to controls ( p < 0.01), further implying the correlation of chronic inflammation and artery stiffness in ME/CFS [ 6 ]. Recent research from Scherbakov and associates (2020), expanded upon the theory of vascular dysfunction in ME/CFS cohorts and found that peripheral endothelial dysfunction (ED) was also associated with increased ME/CFS symptom severity [ 20 ]. The pathogenesis of this mechanism is still not understood but can help provide prognostic information to assess cardiovascular morbidity and mortality in ME/CFS populations [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, an improvement in clinical symptoms could be achieved in seven of the patients, which lasted, in three patients, for more than 12 months [23]. Furthermore, the ME/CFS patients frequently suffer from endothelial dysfunction, which was also improved following IA [26]. These results provided first evidence that IA may be a therapeutic option in ME/CFS patients and the rapid relief from clinical symptoms may be explained by the removal of autoantibodies.…”
Section: Discussionmentioning
confidence: 67%
“…In this report, we presented a case of successfully diagnosed angina masked by ME/CFS deterioration. Endothelial dysfunction was previously correlated to ME/CFS and shown to reflect disease severity [ 11 ]. While the pathophysiology of ME/CFS is not yet fully elucidated [ 12 , 13 ], autonomic nervous system dysregulation, immunological disturbance, viral infections, and metabolic changes were proposed as underlying mechanisms of this malady [ 14 , 15 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial dysfunction was reported to reduce cerebral blood flow, which is correlated with disease severity [ 20 , 21 ], and results in further fatigue [ 22 ]. Therefore, endothelial function might be potentially used to assist the diagnosis of ME/CFS, and serve as an indicator of its severity and the risk of complications [ 7 , 11 ]. The early initiation of treatment is important to improve the prognosis in patients with angina [ 23 ].…”
Section: Discussionmentioning
confidence: 99%